2003
DOI: 10.1038/sj.ijo.0802529
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a rapid weight loss on lipid profile and glycemic control in obese type 2 diabetic patients

Abstract: OBJECTIVE:To test the effect of low calorie diet (LCD) on body weight, lipid profile, and glycemic control in obese type 2 diabetes mellitus (DM) patients. DESIGN: Dietary intervention. SETTING: Department of Human Nutrition, Copenhagen. SUBJECTS: Outpatients: 11 type 2 DM patients (three males/eight females) (10 completed), four on oral hypoglycemic agents (OHA). Body mass index (BMI) 36.875.5 kg/m 2 and age 6275.7 y. INTERVENTIONS: In all, 8 weeks full meal-replacement diet: eight sachets of a nutrition powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 17 publications
8
38
0
2
Order By: Relevance
“…Similar to our results, previous studies have shown a positive association between glycemic control and adiposity (39,42,43) and cholesterol levels (21,44). Studies in individuals without diabetes have also shown similar correlations between lipids and A1C (45)(46)(47)(48).…”
Section: Multivariable Analysessupporting
confidence: 81%
“…Similar to our results, previous studies have shown a positive association between glycemic control and adiposity (39,42,43) and cholesterol levels (21,44). Studies in individuals without diabetes have also shown similar correlations between lipids and A1C (45)(46)(47)(48).…”
Section: Multivariable Analysessupporting
confidence: 81%
“…The present study is similar to the studies performed by Kreisberg [6] and Kesavuler et al [7], Idogun et al [8], Albrki et al [9], Harder H et al [10], and Gordon et al [11]. Similar studies done by Vikram et al in New Delhi showed a significant increase in TGs and high waist to hip ratio in young adults with family history of Type 2 DM [12].…”
Section: Discussionsupporting
confidence: 81%
“…Similar to human, type 2 diabetic rats undergo CR or exercise displayed improved plasma levels of glucose, insulin, cholesterol and triacylglycerol and reduced abdominal fat accumulation [74] . Other report also reported reduction in cardiovascular disease risk in type 2 diabetes following CR [75] . Hammer and colleagues reported that a shortterm very low-calorie diet increases myocardial triglyceride content and is associated with a decrease in left ventricular diastolic function in patients with well-controlled type 2 diabetes [76] .…”
Section: Diabetes Mellitus and Metabolic Syndromementioning
confidence: 89%